Assessing education students’ self-directed learning experiences for optimal online learning - M. Beray, Marisol Jane; M. Cubero, Angelica; G. Casidsid, Robegine; Jade B. Codenera, Rhessan (International Journal of Evaluation and Research in Education (IJERE), 2025)
The advancement of technology enabled the success implementation of online platforms and distance education. Despite its advantages, learners are faced with challenges in the implementation. The study focused on assessing the self-directed learning experiences of education students at Caraga State University Cabadbaran campus, Cabadbaran City, Philippines, in online learning environments. It aimed to assess the self-directed learning experiences concerning learners’ learning motivation, learning style, and technology preparedness. The participants of the study were 154 education students at the College of Industrial Technology and Teacher Education utilizing the descriptive survey research design. The study revealed that students are accountable for their learning, completing activities despite distractions and setting attainable goals. Further analysis showed that learners favor audio-visual learning modalities and have strong self-management skills. However, they may feel less motivated when instructors are not available online to supervise them and felt intimidated when using technological devices. It is suggested that the university should continue promoting and implementing self-directed learning approaches when necessary and offer support like training and resources that cater to learners’ preferences and needs, ensuring a consistent and inclusive application of self-directed learning methodologies for all the participants.